PENGGUNAAN MEDIA ONLINE KOMPAS.COM DALAM MEMENUHI KEBUTUHAN INFORMASI MAHASISWA UPN VETERAN JAKARTA - Marsella Agatha (2021)
This study focuses on knowing the use of online media Kompas.com in meeting the information needs of UPN Veteran Jakarta students. The theory used in this study is the theory of new media. This research uses qualitative method with descriptive type. There were six informants in this study, consisting of students from the Faculty of Medicine, Faculty of Law, and the Faculty of Social and Political Sciences, UPN Veterans Jakarta, who were included in the research criteria. The results of this study indicate that the online media Kompas.com is only used as an initial source in finding information, such as early symptoms of a disease, studying legal and international cases in the news for completion of lecture assignments and research needs for final projects, as well as to find certain definitions in Study of Communication Studies, after which students deepen the information through related books and journals. Online media is used as an implementation study with extensive and related cases from various fields of science.